Prognostic and predictive value of a novel 100-point scale in patients with T1–2N0M0 breast cancer - R. M. Paltuev; A. G. Kudaybergenova; V. F. Semiglazov; A. S. Artemyeva; T. Yu. Semiglazova; A. V. Komyakhov; O. A. Volynshchikova; V. V. Klimenko; M. M. Urezkova (Опухоли женской репродуктивной системы, 2023)
Aim. To increase the efficacy of systemic breast cancer therapy and reduce inappropriate prescriptions using individual immunohistochemical tumor characteristics, as well as to develop prognostic scales to ensure a tailored approach to adjuvant systemic treatment in breast cancer patients.   Materials and methods. We conducted a comprehensive study that included collection of literature data on clinical, pathomorphological, prognostic, and predictive factors of breast cancer, as well as a retrospective cohort study using the data from the cancer registry. We also performed histological and immunohistochemical examination of tumor tissue samples from breast cancer patients (for the retrospective cohort study) and statistical data analysis. A total of 1,216 patients with T1–2N0M0 breast cancer were included in this study. Histological and immunohistochemical examinations of tissue samples (paraffin blocks) were conducted in the laboratory of N. N. Petrov National Medical Research Center of Oncology. We stained slides for both routinely used markers (including estrogen receptors, progesterone receptors, HER2, and Ki-67) and other markers (CK14, FOXA1, FOXP3, PD-L1, P53, SMA, androgen receptors, E-cadherin, CD4, CD8, CK5 / 6, EGFR).We analyzed risk factors for lethal outcomes in patients from this group to develop prognostic scales and compared their results.   Results. We evaluated the most clinically and statistically significant factors affecting mortality. Using logistic regression, we chose 10 factors that had the greatest impact on the outcomes and then produced several scales, includinga 10-point regression scale (based on 10 most significant factors identified). Survival analysis in high-risk and low-risk patients using the regression scale demonstrated significant differences between these groups (р <0.00001). The assessment of adjuvant chemotherapy efficacy in the combined group of intermediate- and high-risk patients (as estimated by the regression model) showed that intermediate- and high-risk patients receiving adjuvant chemotherapy had significant differences in their survival (р = 0.0057). The regression scale for 10-year prognosis demonstrated sufficient sensitivity (58.05 %), specificity (69.47 %) and ef fectiveness (63.76 %).   Conclusion. Our regression prognostic scale includes markers with a high prognostic value. The multifactorial approach used in the developed regression scale for breast cancer 10-year prognosis increases its accuracy and reliability.